Traumas of Acting Physical and Psychological Violence: How Fact and Fiction Shape Bodies for Better or Worse. (1st July 2013) - Seton, Mark Cariston
Violation and injury (both physical and psychological) are aspects of life and therefore figure significantly; not only in much dramatic storytelling, but also in the life circumstances that doctors, nurses, emergency professionals and even the military encounter. However, in theatrical, cinematic or simulated performance of violence, little attention is paid to possible traumatization of participants and those who witness such dramatizations. Such performances are deemed merely fictions or simulations, and are therefore considered benign. However, experts in trauma have found that the body does not distinguish between cognitively understood fiction and perceived experience. Therefore, management of traumatization requires both cognitive awareness and embodied engagement with the possibilities of traumatization. What is needed is greater duty of care in preparing those participating in theatrical, cinematic and simulated performances of violence to become more resiliently vulnerable, so that they can support themselves and their peers in negotiating the inevitability of trauma.